Impact of high-altitude acclimatization and de-acclimatization on the intestinal microbiota of rats in a natural high-altitude environment - Hao, Doudou; Niu, Haomeng; Zhao, Qin; Shi, Jing; An, Chuanhao; Wang, Siyu; Zhou, Chaohua; Chen, Siyuan; Fu, Yongxing; Zhang, Yongqun; He, Zeng (Frontiers in Microbiology, 2024)
Intestinal microorganisms play an important role in the health of both humans and animals, with their composition being influenced by changes in the host's environment. We evaluated the longitudinal changes in the fecal microbial community of rats at different altitudes across various time points. Rats were airlifted to high altitude (3650 m) and acclimatized for 42 days (HAC), before being by airlifted back to low altitude (500 m) and de-acclimatized for 28 days (HADA); meanwhile, the control group included rats living at low altitude (500 m; LA). We investigated changes in the gut microbiota at 12 time points during high-altitude acclimatization and de-acclimatization, employing 16S rRNA gene sequencing technology alongside physiological indices, such as weight and daily autonomous activity time. A significant increase in the Chao1 index was observed on day 14 in the HAC and HADA groups compared to that in the LA group, indicating clear differences in species richness. Moreover, the principal coordinate analysis revealed that the bacterial community structures of HAC and HADA differed from those in LA. Long-term high-altitude acclimatization and deacclimatization resulted in the reduced abundance of the probiotic Lactobacillus. Altitude and age significantly influenced intestinal microbiota composition, with changes in ambient oxygen content and atmospheric partial pressure being considered key causal factors of altitude-dependent alterations in microbiota composition. High-altitude may be linked to an increase in anaerobic bacterial abundance and a decrease in non-anaerobic bacterial abundance. In this study, the hypobaric hypoxic conditions at high-altitude increased the abundance of anaerobes, while reducing the abundance of probiotics; these changes in bacterial community structure may, ultimately, affect host health. Overall, gaining a comprehensive understanding of the intestinal microbiota alterations during highaltitude acclimatization and de-acclimatization is essential for the development of effective prevention and treatment strategies to better protect the health of individuals traveling between highand low-altitude areas.